Evaluation of Early and Midterm Mitral Valve Repair Results in Consecutive Severe Mitral Regurgitation Patients - Uygur, Feragat; Deniz, Hayati (Progress in Nutrition, 2022)
Study Objectives: Surgical valve repair for mitral regurgitation has significant advantages over valve replacement. In this study, we aimed to investigate the early and mid-term results of mitral valve repair using current techniques in order to find out independent risk factors affecting the early and mid-term outcomes. Methods: We retrospectively studied firstly 192 consecutive adult patients (mean age: 43.2±12.3; 120 females and 72 males) who underwent primary mitral valve repair between January 2012 and July 2018. Risk factors affecting the need for re-operations and late survival were determined via univariate and multivariate analyses. Actuarial survival and event-free curves were compared by linear regression analysis. Results: Operative mortality was 2.6% (5 deaths 0–30th. postoperative day (POD). Late mortality was 3.7% (7/187). Reoperation was required in 16 (8.3%) patients. Kaplan–Meier actuarial survival was 95.8%±2.3% at a mean of 43 months. Survival free from reoperation was 92.8%± 4.2% at 60 months. Multivariate analysis demonstrated that residual NYHA class III and IV, low preoperative ejection fraction, and ischemic MR were independent predictors of mortality. Conclusion: We concluded that mitral valve repair showed excellent survival (except ischemic MR), acceptable re-operation rate with satisfactory valve function in a mid-term follow-up period.